Blood picture of lead acetate toxicity in chicken - Imad Ibrahim Ali Al-Sultan; O. E.Ibrahim; T.A. Makkawi (2011)
The study was designed to evaluate the hematological changes in acute and chronic toxicity in chicken experimentally induced with lead acetate and treated with 5% calcium disodium edetate. Sixty five 7 week-old broiler chicken of Ebba2000 breed were used in the experiment. A total of 21 birds were used to estimate the toxic dose and were divided into 7 groups. Each group of 3 birds was treated with different doses of lead acetate. The toxic dose was found to be 2 gm/kg bw. The remaining 44 broilers were divided into 5 groups, four of them of 10 birds each. The fifth group of 4 broilers was not treated and used as a control. To induce acute and Chronic toxicity with the lead compound, both groups 1 & 2 were given the toxic dose in an amount of 2 gm/kg bw, while groups 3 & 4 were given a dose of 1 mg/kg bw. Both groups 2 & 4 were treated with 5% calcium disodium edetate immediately after the appearance of the toxicity signs. Hematological values taken from the birds that developed chronic toxic pathological changes were higher than that of the birds with the acute form of toxicity. However, there was a negative correlation between the concentration of lead in the blood and the intensity of damage to the tissues and organs.